Predicting liver cancer on epigenomics data using machine learning - Vekariya, Vishalkumar; Passi, Kalpdrum; Jain, Chakresh Kumar (Frontiers in Bioinformatics, 2022)
Epigenomics is the branch of biology concerned with the phenotype modifications that do not induce any change in the cell DNA sequence. Epigenetic modifications apply changes to the properties of DNA, which ultimately prevents such DNA actions from being executed. These alterations arise in the cancer cells, which is the only cause of cancer. The liver is the metabolic cleansing centre of human body and the only organ, which can regenerate itself, but liver cancer can stop the cleansing of the body. Machine learning techniques are used in this research to predict the gene expression of the liver cells for the Liver Hepatocellular Carcinoma (LIHC), which is the third biggest reason of death by cancer and affects five hundred thousand people per year. The data for LIHC includes four different types namely, methylation, histone, the human genome and RNA-Sequences. The data was accessed through open source technologies in R programming languages for The Cancer Genome Atlas (TCGA). The proposed method considers 1000 features across the four types of data. Nine different feature selection methods were used and eight different classification methods are compared to select the best model over 5-fold cross validation and different training-to-test ratios. The best model was obtained for 140 features for ReliefF feature selection and XGBoost classification method with an AUC of 1.0 and an accuracy of 99.67% to predict the liver cancer.